PERANCANGAN SISTEM PEMASANGAN IKLAN ONLINE PADA APLIKASI E-COMMERCE (E-GEMANUSA) MENGGUNAKAN METODE RESTFUL API DAN FRAMEWORK LARAVEL - Sutrisno Sutrisno; Mursalat Asyidiq; Sugeng Santoso (Jurnal Ilmiah Sains dan Teknologi, 2018)
ABSTRACT E-gemanusa is an electronic commerce system (e-commerce) developed and used by PT. Gemanusa Sentra Teknologi. E-gemanusa is made as a promotional media of products and services sold by PT. Gemanusa Sentra Teknologi. Base dont here sults of research e-gemanusa system still has some short comings. To solve an existing problem the author uses the REST Ful API method as a data transfer method and uses UML as a method of depiction of the system. With this advertising system will facilitate users in the process of marketing products or services. The use of REST Ful API method will simplify the process of system development and system integration with various platforms. By dividing the system into multiple micro service scane ase the system work load.